2016
DOI: 10.11591/535
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Superconducting Fault Current Limiterin DC System with Renewable Energy Sources

Abstract: Superconducting fault-current limiters (SFCLs) have been the subject of research and development for many years and offer an attractive solution to the problem of rising fault levels in electrical distribution systems. SFCLs can greatly reduce fault currents and the damage at the point of fault, and help improve the stability of a power system. Superconducting fault-current limiters (SFCL) provide a new efficient approach to the reliable handling of such faults.(SCFLs) can be used for various nominal voltages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was found that the fault current contribution of a DG resource can be controlled by placing the fault current limiter in series with the DG unit. Various methods of [15][16][17], for safeguarding the protection devices from fault current increment. This paper will investigate the impact of DG installation at the optimal location to the fault current increment in power distribution systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the fault current contribution of a DG resource can be controlled by placing the fault current limiter in series with the DG unit. Various methods of [15][16][17], for safeguarding the protection devices from fault current increment. This paper will investigate the impact of DG installation at the optimal location to the fault current increment in power distribution systems.…”
Section: Introductionmentioning
confidence: 99%